Terry Gilliam - Marks, Peter, 1958- (Manchester Gothic (Manchester, England)., 2017)
This book is the most sustained and comprehensive examination to date of one of cinema's most challenging and lauded auteur. It proposes new ways of seeing Gilliam and his films that go beyond reductive readings of him as a gifted but manic fantasist. It analyses Gilliam's work over nearly four decades, from Monty Python, to Brazil and Tideland.